(Desperately) Seeking Service Leadership in Academic Libraries: An Analysis of Dean and Director Position Advertisements. Issue 1 (2nd January 2018) - L. Maciel, Michael; Kaspar, Wendi Arant; vanDuinkerken, Wyoma
ABSTRACT: Given the continual rate of change in academic libraries, the increasing accountability in higher education and the call to contribute to learning outcomes, career success, and lifelong learning, leadership that is responsive to the service mission is critical to their success and evolution. However, as has been consistently stated in the literature, there is a leadership vacuum. The pursuit of leadership, as evidenced by job advertisements, is representative of this lack of attention to a service leadership ethic. This study examines library dean and director position descriptions and advertisements from 2011 to 2015 for elements of the service leadership model. Analysis indicates that most leadership posting for academic libraries attend to traditional library experience and management skills, rather than service leadership attributes. Examples of framing positions based on the service leadership model are also provided.